A Comparative Analysis of the Royalty Sharing Rules of the Spotify Digital Music Player Service Channel in Europe and Indonesia - I Made Nara Virjana (POLICY, LAW, NOTARY AND REGULATORY ISSUES, 2025)
The development of digital technology has transformed the way music is consumed, with streaming platforms such as Spotify, YouTube Music, and Apple Music becoming the primary channels for music distribution. In Indonesia, the use of digital music services continues to grow, creating significant opportunities for the music industry while also presenting challenges related to fair royalty distribution mechanisms. This study aims to conduct a comparative analysis of royalty distribution regulations in digital music streaming services, particularly Spotify, in Europe and Indonesia. This study employs a normative juridical method with a comparative legal approach, analyzing secondary data consisting of legislation, legal documents, court decisions, and relevant literature through a descriptive-analytical framework to compare digital music royalty distribution regulations in Europe and Indonesia. The study shows that royalty distribution regulations in Indonesia, particularly those referring to Government Regulation No. 56 of 2021, still face uncertainties in implementation, especially regarding royalty distribution for independent musicians and digital service providers. Although efforts have been made to manage copyright through the National Collective Management Organization, the mechanisms for royalty collection and distribution are hindered by poor coordination between institutions and a lack of transparency in music usage reports. A comparison with regulations in the European Union indicates that Indonesia needs to adjust its regulations to better align with the complexities of the current digital music market. To establish a fair and transparent royalty distribution system in Indonesia, more comprehensive regulatory improvements and better coordination among relevant institutions are necessary.